1980
DOI: 10.1021/jm00181a007
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted azole derivatives. 1. Synthesis and antiinflammatory activity of some 2-(substituted-pyridinyl)benzimidazoles

Abstract: A series of 2-(2-pyridinyl)benzimidazoles was synthesized and evaluated for antiinflammatory activity by the carrageenan-induced rat paw edema assay. Among several active derivatives, 2-(5-ethylpyridin-2-yl)benzimidazole (6) was selected for further study. A comparison of compound 6 with phenylbutazone and tiaramide revealed that 6 possesses stronger activity in acute inflammatory models possibly with slightly less gastrointestinal irritation than both phenylbutazone and tiaramide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 2 publications
0
40
0
Order By: Relevance
“…These compounds exhibit a wide spectrum of biological and pharmacological activities [1][2][3][4][5][6][7]. Also, 2-aryl benzimidazole derivatives are fluorescent acid-base indicators [8], dopants for plastic scintillation applications [9] and subunits of polybenzimidazoles as thermally stable polymers [10].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds exhibit a wide spectrum of biological and pharmacological activities [1][2][3][4][5][6][7]. Also, 2-aryl benzimidazole derivatives are fluorescent acid-base indicators [8], dopants for plastic scintillation applications [9] and subunits of polybenzimidazoles as thermally stable polymers [10].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, they gained much attention as important pharmacophore and privileged structure in medicinal chemistry [6,7] encompassing a diverse range of biological activities including antibacterial [8,9], anti-parasitic agent [10], antihistamine [11,12], antiulcerative [13], antioxidant [14], antiallergic [15], anticancer activities [16], anti-HIV-1 [17], anti-herpes (HSV-1) [18], and for the treatment of Hepatitis C and B viruses [19,20]. Finally, 2-substitutd benzimidazoles [21,22] and other benzimidazole derivatives [23][24][25] were reported to exhibit anti-inflammatory and analgesic properties. Thus, the unique structural features and pharmaceutical activities of benzimidazoles have encouraged us to synthesize novel 2-methyl-N-substituted benzimidazolesugar conjugates and study their anti-inflammatory and analgesic activities.…”
Section: Introductionmentioning
confidence: 99%
“…They have a wide range of biological and pharmacological activities with therapeutic potential. Substituted benzimidazole derivatives have different therapeutic applications, including anti-histamine [12], anti-ulcerative [13], anti-inflammatory [14], anti-oxidant [15], anti-HIV-1 [16], anti-bacterial [17] and anti-cancer activities [18]. We previous reported that benzimidazole derivatives (FPipTB and MPTB) induced cell apoptosis in chondrosarcoma cells [19,20].…”
Section: Introductionmentioning
confidence: 99%